A way forward for climate technology transfer and sustainable development goals. Issue 142 (April 2023) - Kim, Whijin; Song, Cholho; Lee, Sue Kyoung; Choi, Gayoung; Yang, Rywon; Bak, Inhye; Lee, Woo-Kyun
Abstract: The 2015 Paris Agreement, which was a global effort to address climate change and meet Sustainable Development Goals (SDG), established the Technology Mechanism Initiative as the key to facilitating technology transfer; however, the target SDGs of this initiative have not been identified. This study reviewed technical assistance (TA) project documents of the Climate Technology Centre and Network (CTCN), an organization under the Technology Mechanism Initiative, to analyze the general status of climate technology implementation, identify the targeted SDGs using sectoral classification, and examine the current national SDG statuses of TA-participating countries. While sectoral classifications have specific relationships with certain goals, SDGs 7 (Affordable and Clean Energy), 8 (Decent Work and Economic Growth), 9 (Industry Innovation and Infrastructure), and 13 (Climate Action) were primarily referenced as they focused on energy and cross-sector applications. The evaluations also revealed that countries should prioritize poverty- and food-related SDGs. Therefore, expanding TA contributions to SDGs by better grouping sectoral classifications based on regional and local needs was essential because SDGs were linked to both sector-specific and climate technologies. Thus, a climate technology package based on sectoral classifications was proposed to bridge the gap between SDG attainment and the climate change objectives proposed by the Paris Agreement. Highlights: Sustainable Development Goals (SDGs) targeted by technology assistance projects were identified. Energy and cross-sector SDGs were the most commonly mentioned, but not food and poverty SDGs. A climate technology package is proposed based on sectoral classifications and regional needs. Technologies should be grouped according to their priority to accelerate sustainable development.